EVALUASI WASTE PADA PROSES SPOT WELDING MELALUI PENDEKATAN VALUE STREAM MAPPING - Khamaludin, Khamaludin; Maulidani, Bagas Caesar (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2025)
PT. STE produces small bracket parts for four-wheeled vehicles. In July – September 2024, transport hook products are experiencing a significant increase in demand compared to other products. It is known that in the production process of this transport hook there are still obstacles or activities that do not add value to the company. Therefore identification of waste is carried out in order to minimize the occurrence of this waste. The purpose of this research is to identify and minimize waste in the spot welding production process and determine the takt time in the hook transport production process. The method used is Value Stream Mapping (VSM. The results of the current state value stream mapping analysis before making improvements in the form of minimizing things that do not provide added value to the hook transport production process get a cycle efficiency process value of 74%, while in the expected future state value stream mapping analysis efforts are made to minimize waste and improve value added activity by obtaining a cycle efficiency process value of 94% or increase of 20% and the results of the analysis by calculating the take time in the spot welding production process is equal to 52.85 seconds, this means that in carrying out the hook transport production process it takes 52.85 seconds/product to be able to fulfill requests from consumers